2017
DOI: 10.1515/eurodl-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Transactional Distance Dialogic Interactions and Student Satisfaction in a Multi-Institutional Blended Learning Environment

Abstract: This study explored the impact of transactional distance dialogic interactions on student satisfaction in an international blended learning master's degree program. The program examined was collaboratively delivered by three European universities to a cohort of students residing on several different continents. Students reported experiencing transactional distance for learnerlearner and learner-teacher dialogic interaction elements and dissatisfaction in the online components of the program but reported a sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
2
11
0
1
Order By: Relevance
“…On the other hand, Cao and Sakchutchawan (2011) reported how students enrolled in MBA online courses were dissatisfied with their online learning experience while still performing as well as their face-to-face peers. Similar findings were reported by Best and Conceição (2017) in their study on distance interaction in a multi-institutional environment, where the majority of students reported that their experience with distance learning components on the programme did not meet their learning needs as much as the face-to-face ones.…”
Section: Distance Learningsupporting
confidence: 84%
See 2 more Smart Citations
“…On the other hand, Cao and Sakchutchawan (2011) reported how students enrolled in MBA online courses were dissatisfied with their online learning experience while still performing as well as their face-to-face peers. Similar findings were reported by Best and Conceição (2017) in their study on distance interaction in a multi-institutional environment, where the majority of students reported that their experience with distance learning components on the programme did not meet their learning needs as much as the face-to-face ones.…”
Section: Distance Learningsupporting
confidence: 84%
“…Students selecting part time programmes do so in an attempt to reconcile their academic career with working and family commitments (Taylor, Dunn & Winn, 2015) and increasing numbers of institutions around the would offer this typology of delivery, usually in addition to the standard full time option (Grabowski et al, 2016). Conversely, examples of dual or multiinstitutional collaborations are still scarce (Best & Conceição, 2017) and involving an additional set of aspects to consider, such as individual decision-making processes, different systems for assessing and grading the students, different financial conditions and different support to the use of technologies (Larsson et al, 2005).…”
Section: Distance Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…the transactional distance between student and teacher, student and student, and student and content, were significant predictors of student satisfaction in an online environment, with the student-teacher transactional distance being the stronger predictor. Best and Conceicao (2017) explored the impact of transactional distance dialogic interactions on student satisfaction in an international blended learning master's degree program. The participants reported experiencing transactional distance for learner-learner and learner-teacher dialogic interaction elements and dissatisfaction in the online components of the program, but reported a sense of community and satisfaction for the face-to-face (in-person) elements of the program.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hoffman, etc. ), with which they can be presented [15]. This is the Moodle Internet platform, as it is specially designed for educational purposes and is officially accepted in these educational institutions.…”
Section: Suggested Correlation With Organizational Aspects Of Learningmentioning
confidence: 99%